A theory of the COVID-19 pandemic’s impact on the government-citizen relationship - Luartz, Lewis Alexander (Monitor ISH, 2023)
This paper explores how crises, such as the COVID-19 pandemic, can impact political behavior amid restrictions. Specifically, this paper builds a theoretical model suggesting the pandemic promoted restriction-oriented policies from the government in response to the crisis while promoting populist tendencies among citizens who disagree with those policies. Moreover, through a formal two-player extensive form game, the model promoted in this paper suggests restrictions are unpopular enough that citizens may push back on such policies regardless of crisis severity. The theoretical outcomes here have significant implications on governance, given that politicians care about re-election.
Keywords: COVID-19; demokracija; notranja politika; pandemije; populizem; vlada